Conversations About End-of-Life Decisions in Neonatology: Do Doctors and Parents Implement Shared Decision-Making? - Schouten, Esther S.; Beyer, Maria F.; Flemmer, Andreas W.; de Vos, Mirjam A.; Kuehlmeyer, Katja (Frontiers in Pediatrics, 2022)
Introduction Advances in perinatal medicine have contributed to significantly improved survival of newborns. While some infants die despite extensive medical treatment, a larger proportion dies as a consequence of medical decision-making (MDM).(1, 2) International guidelines about end-of-life (EOL) MDM for neonates unify in their recommendation for shared decision-making (SDM) between doctors and parents.(3-8) Yet, we do not know to what extent SDM is realized in neonatal practice. Objective We aim at examining to which extent SDM is implemented in the NICU setting. Methods By means of Qualitative Content Analysis, audio-recorded conversations between neonatologists and parents were analyzed. We used a framework by de Vos that was used to analyze similar conversations on the PICU. Results In total we analyzed 17 conversations with 23 parents of 12 NICU patients. SDM was adopted only to a small extent in neonatal EOL-MDM conversations. The extent of sharing decreased considerably over the stages of SDM. Neonatologists used a double bind communication in which they suggested to find a decision together with parents, while at the same time seeking parents’ agreement for the intended decision to forgo life-sustaining treatment. Conclusions Since SDM was only realized to a small extent in the NICU under study, we suggest evaluating how parents in this unit experience the EOL-MDM process and whether they feel their involvement in the process acceptable and beneficial. If parents evaluate their involvement in the current approach beneficial, the need for implementation of SDM to the full extent, as suggested in the guidelines, may need to be critically re-assessed.